STEAM APPROACH IN TEACHING FOREIGN LANGUAGES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article has been written to help teachers to increase the pupils` language skills, STEAM stands for Science, Technology, Engineering, Art, and Math. Each of STEAM’s five subjects share a common approach and focus. They require gathering and using evidence to create knowledge or solve problems. STEAM learning happens naturally everyday as children explore, play, and try new things. When young children have the opportunity to investigate the world around them, they learn and experiment with new STEAM skills and theories. Research shows there is a positive relationship between early STEAM experiences and future success in school. It provides an interactive learning experience and is intended as a professional development resource to help supervisors, coordinators, managers, and education staff understand how young children engage with STEAM concepts and ideas. This document will also help adults identify strategies for exploring and developing STEAM in early learning settings.